A Study of the Anthropometric Dimensions of the Lower Body of Young Men in Western China (Journal of Fiber Bioengineering and Informatics, 2014)
A survey was performed to measure the anthropometric dimensions of 201 young men, with ages rangingfrom 18-28 years, in Western China. A total of 25 anthropometric dimensions were measured for theseyoung men. Mean values, standard deviations, 5th, 50th and 95th percentiles for these anthropometricdimensions and 7 body proportions were determined. Subsequently, the anthropometric dimensions ofthese young men were compared with those from central and eastern regions of China and also nationalstandards. It was found that the body shapes of the young Western Chinese men were significantlydifferent from those of other regions. In addition, the following five factors were identified, according toa factor analysis of the data obtained in the study: waist girth, abdominal girth and waist height, asbeing the most important anthropometric variables to be considered when designing trousers.